Feasibility of flowcytometric quantitation of immune effector cell subsets in the sentinel lymph node of the breast after cryopreservation - van Pul, Kim M.; Vuylsteke, Ronald J.C.L.M.; Bril, Herman; Stockmann, Hein B.A.C.; de Gruijl, Tanja D. (Journal of immunological methods, 2012)
The sentinel lymph node (SLN) is an emerging focus for immunological research in breast cancer. Cryopreservation of SLN single-cell suspensions allows for simultaneous phenotypic multi-parameter analyses and minimizes operator dependent variability. This is of particular importance for immunomonitoring of large multicenter trials. However, little data are available regarding the influence of cryopreservation on phenotypic characteristics of lymph node dendritic cells and T cells. In this study we assessed the feasibility of cryopreservation of viable SLN cell samples for flowcytometric analysis, by comparing quantitative analyses of SLN cell samples after freeze-thawing with direct analysis of fresh SLN cell samples. SLN were collected from nine breast cancer patients. From each SLN cell sample, half was used for immediate analysis and half was analyzed after cryopreservation and thawing. Conventional dendritic cell (cDC) and T cell subsets were quantified and phenotypically characterized by flow cytometry. The observed frequencies of both CD1a+ and CD1a−CD11c+CD14− cDC subsets showed significant correlation between the fresh and frozen-thawed samples. Similar high correlations were found for CD83 and CD86 expression markers on the more frequent (>0.2%) CD1a+ and CD1a−CD11c+CD14− cDC subset, but not on the low-frequency (<0.2%) CD1a+CD11c+CD14+ cDC subset. CD4/CD8 T cell ratios were comparable and were significantly correlated pre- and post-freezing. Regulatory CD4+CD25hi T cell frequencies and their FoxP3 expression levels were significantly higher after freezing–thawing than in the freshly analyzed samples. Nevertheless, a highly significant correlation was found for both parameters pre- and post-freezing. Cryopreservation and thawing seems a valid and practical alternative to direct analysis of fresh viable lymph node cells, without introducing cryo-dependent variance between SLN samples. However, enumeration of low-frequency cell populations and assessment of their marker expression levels are less reliable after cryopreservation and should be assessed and considered in the design of each clinical trial. ► Sentinel lymph node (SLN) is a popular focus for tumor immunological research. ► Influence of cryopreservation on phenotype of SLN cDC- and T-cells is not known. ► Flowcytometric analyses of fresh and cryopreserved SLN samples were compared. ► cDC and T cell frequencies correlated significantly pre- and post-cryopreservation. ► Cryopreservation is a valid alternative to direct analysis of fresh lymph node cells.